Converting an amorphous covalent organic polymer to a crystalline covalent organic framework mediated by a repairing agent. Issue 17 (8th February 2023) - Han, Xiang-Hao; Liang, Rong-Ran; Zhou, Zhi-Bei; Qi, Qiao-Yan; Zhao, Xin
Abstract : This study demonstrates that monofunctional molecules can work as repairing agents to promote conversion from amorphous cross-linked polymers to crystalline covalent organic frameworks (COFs), which could be a new method for the construction of COFs. Abstract : We herein report a new approach to converting an amorphous covalent organic polymer to a crystalline heteropore covalent organic framework (COF), which is promoted by using an additive for structure repair. This provides a new method for the construction of COFs from cross-linked polymers.